Burden and Outcomes of Severe Lower Respiratory Tract Infections with Unknown Etiology: A Retrospective Observational Study on Epidemiological Trends Over an 8-Year Period (2016–2024) - Giovanni Scaglione; Marta Canuti; Martina Offer; Valentina Breschi; Antonio Piralla; Fausto Baldanti; Gabriele Del Castillo; Francesco Scovenna; Sabrina Buoro; Federica Morani; Danilo Cereda; Alessandra Bandera; et al. (Infectious Diseases and Therapy)
Abstract Introduction Severe lower respiratory tract infections often require hospitalization, but a significant proportion lack microbiological diagnosis, leading to challenges in management. This study aimed to compare clinical outcomes of S-LRTIs with unknown versus known bacteria or viral etiology in Lombardy, Italy. Methods A retrospective study analyzed respiratory infection-related hospitalizations in Lombardy over 8 years (2016–2024) using patient discharge charts. Patients were categorized into four groups: bacterial, viral (non-COVID-19), COVID-19-related, and unknown etiology. Outcomes included length of stay, intensive care unit admissions, and intra-hospital mortality. Temporal, seasonal, and age-specific trends were evaluated. Results Among 683,741 hospitalizations, 338,211 (49.5%) were of unknown etiology, showing a 12.3% intra-hospital mortality rate (41,627 deaths) and 4.0% intensive care unit admission rate (13,625 admissions). COVID-19-related hospitalizations had the highest intra-hospital mortality rate (22.0%, 36,446 deaths in 165,605 COVID-19-related hospitalizations) and number of intensive care unit admissions (14,725 admissions, 8.9% of COVID-19-related hospitalizations), while viral non-COVID-19 hospitalizations showed the lowest intra-hospital mortality rate (3.2%, 1114 deaths in 34,769 viral-non-COVID-19 hospitalizations) and shortest length of stay (11.9 days). Hospitalizations with unknown etiology were more common in minors (42,190 episodes, 57.6% of total in < 18 years) and elderly (358,534 episodes, 56.2% of total in > 75 years), especially during warm seasons. Post-pandemic years saw increased bacterial and viral hospitalizations alongside a reduced proportion of those without an unknown etiology. Conclusions Respiratory infection-related hospitalizations with unknown etiology are associated with distinct seasonal and demographic patterns, and poorer outcomes compared to viral non-COVID-19 hospitalizations. COVID-19 reshaped S-LRTI epidemiology and diagnostic approaches, highlighting the need for comprehensive pathogen panels and tailored management strategies, while promoting their expanded use. Future research should integrate detailed clinical data to improve understanding and outcomes of severe respiratory infections, especially in vulnerable populations.